2020
DOI: 10.1186/s12872-020-01372-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of morphometry and ventricular function of healthy and smoking young people

Abstract: Background: Tobacco smoke is one of the most significant risk factors for cardiovascular diseases and damages in the myocardial tissue directly. Cardiac magnetic resonance (CMR) has been used and is a promising tool to evaluate morphometry and cardiac function in humans. The objective of this study was to evaluate associations of smoking with morphometry and cardiac function by CMR technique in young adult smokers. Methods: Altogether, 49 volunteers (22 smokers and 27 non-smokers) were included in the study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Larger patient cohorts are necessary for further investigation to validate these differences. Consistent with our findings, obesity and smoking in adolescents have been linked to increased left ventricular volume and reduced myocardial diastolic function ( 20 , 31 , 32 ). Our study also depicted the impact of BMI on cardiac function, but no significant correlation was seen between smoking and cardiac function parameters, potentially due to the limited number of smokers included in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Larger patient cohorts are necessary for further investigation to validate these differences. Consistent with our findings, obesity and smoking in adolescents have been linked to increased left ventricular volume and reduced myocardial diastolic function ( 20 , 31 , 32 ). Our study also depicted the impact of BMI on cardiac function, but no significant correlation was seen between smoking and cardiac function parameters, potentially due to the limited number of smokers included in our study.…”
Section: Discussionsupporting
confidence: 92%
“…To accurately evaluate changes in cardiac function in diabetic cardiomyopathy, this study excluded patients with hypertension, coronary heart disease, and valvular disease. Patients with T2DM were matched with healthy individuals based on BMI, gender, age, and smoking status to minimize the impact of these factors on cardiac function ( 19 , 20 ). The findings underscored impaired diastolic function in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…After multivariate regression analysis, smoking was significantly correlated with the GWI, GWW and GWE, indicating that smoking impairs myocardial function. There is evidence that nicotine can cause direct damage to the structure and function of the heart even in patients without atherosclerosis or other chronic diseases related to the risk of cardiovascular disease [ 35 ], and the amount of smoking is positively correlated with the degree of impairment of cardiac systolic function [ 36 ]. In the Multi-Ethnic Study of Atherosclerosis (MESA) study, it was found that the LV mass and geometry were associated with the occurrence of HF, stroke and coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoking is the world's leading cause of preventable death, with more than 7 million deaths every year, worldwide (1)(2)(3). Tobacco consumption is a known risk factor associated with disease development and mortality by cancer, cardiovascular disease, and respiratory disease (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%